Polymerase chain reaction for detection of Leptospira spp. in clinical samples. - Mérien, F (1992)
A sensitive assay for Leptospira spp., the causative agent of leptospirosis, was developed on the basis of the polymerase chain reaction (PCR). A 331-bp sequence from the Leptospira interrogans serovar canicola rrs (16S) gene was amplified, and the PCR products were analyzed by DNA-DNA hybridization by using a 289-bp fragment internal to the amplified DNA. Specific PCR products also were obtained with DNA from the closely related nonpathogenic Leptospira biflexa but not with DNA from other spirochetes, such as Borrelia burgdorferi, Borrelia hermsii, Treponema denticola, Treponema pallidum, Spirochaeta aurantia, or more distant organisms such as Escherichia coli, Staphylococcus aureus, Mycobacterium tuberculosis, and Proteus mirabilis. The assay was able to detect as few as 10 bacteria. Leptospira DNA was detected in urine from experimentally infected mice. In addition, the test was found to be suitable for diagnosing leptospirosis in humans. Cerebrospinal fluid and urine from patients with leptospirosis were positive, whereas samples from control uninfected patients were negative.